Empowering Hispanic Multiunit Housing Residents to Advocate for Smokefree Policies: A Randomized Controlled Trial of a Culturally Tailored Fotonovela Intervention - Jennifer B. Unger; Daniel W. Soto; Angelica Delgado Rendon; Lourdes Baezconde-Garbanati; Tess Boley Cruz (Mary Ann Liebert, 2019)
Purpose: Hispanic residents of multiunit housing (MUH) are disproportionately exposed to secondhand (SHS) and thirdhand tobacco smoke (THS) from neighboring apartment units and common areas. Comprehensive legislation and voluntary policies are needed to protect residents from smoke. We developed a culturally tailored bilingual fotonovela to educate Hispanic residents about SHS and THS and encourage them to talk to their neighbors and landlords about reducing smoke exposure. This article describes a randomized controlled trial of the fotonovela. The objective of the study was to evaluate the effect of the fotonovela on knowledge, attitudes, and behavioral intentions about reducing smoke exposure. Methods: Hispanic MUH residents (N=403) completed a survey and were randomly assigned to receive the fotonovela, a text pamphlet, or no materials. They completed a follow-up survey 6 months later. Results: Among the entire sample, there were no significant differences across the three groups in knowledge or attitudes at follow-up. However, when the analyses were restricted to respondents who actually read part or all of the booklets (77% in the fotonovela group and 71% in the text pamphlet group), there were significant differences in two of the six outcome measures; those who read the fotonovela had higher scores on self-efficacy to talk to others about smoke and positive attitudes toward advocacy actions, relative to those who read the text pamphlet. Conclusion: Results indicate that a fotonovela can be an effective tool to empower Hispanic MUH residents to advocate for voluntary smokefree policies, but more efforts are needed to encourage residents to read the materials.